Addressing Juvenile Protection Discrepancies: A Study on Legal Safeguards and Challenges against Sexual Abuse by Educators in Seluma Regency - Pradityo, Randy; Rahmasari, Helda; Ramadhani, Susi; Suhertini, Sakinah; Lekattia, Kurnia (The Indonesian Journal of International Clinical Legal Education, 2023)
Law Number 11 of 2012, commonly referred to as the Juvenile Criminal Justice System Law, stands as a legal framework designed to safeguard children entangled in legal conflicts. Its primary objective is to secure a promising future for these children, facilitating opportunities for identity development that fosters independence, responsibility, and constructive contributions to themselves, their families, society, and the nation. Despite the existence of these legal safeguards, their efficacy often encounters challenges within the intricate dynamics of social life. This disjunction is particularly conspicuous in institutional environments such as schools, where the assurance of safety is not guaranteed. Disturbingly, statistical data compiled by the PPA Unit of the Criminal Investigation Unit of the Seluma Police spanning from 2019 to 2021 reveals a disconcerting prevalence of eight cases of sexual abuse perpetrated by teachers against their students. A poignant instance unfolded in Talang Alai Village, Kec. Air Periukan District, wherein a child named RA became a victim of molestation by an individual identified by the initials AI on August 18, 2019. In response to these distressing occurrences, this research endeavors to formulate strategies for addressing criminal acts of sexual abuse committed by teaching staff in Seluma Regency. The study aims to meticulously scrutinize and analyze the prevalence of such crimes, providing scholarly insights into the harsh reality of sexual abuse committed by teaching staff in this specific region.